The Effect Of Discovery Learning Model On Students Learning Outcomes On Work And Energy Material At SMA Negeri 1 Saipar Dolok Hole - Situmorang, Mirna Wanty; Harahap, Mukti Hamjah ((IPER) Indonesian Physics Education Research, 2024)
This study aims to determine the effect of the Discovery Learning model on students™ learning outcomes in the subject of Work and Energy in class X SMA Negeri 1 Saipar Dolok Hole. This type of research is a quasi-experimental. The population of this research were all of students X MIPA and the samples were X MIPA 1 as the experimental class and class X MIPA 2 as the control class, each class consisting of 30 people. The instrument was in the form of 10 essay test which have been validated. Learning outcomes were measured through the pre-test and post-test. Based on the results of the study, pre-test mean value of the experimental class was 30,17 and for the control class was 26,33. The results of testing the hypothesis obtained tcount<ttable=1,750<2,002 using Î±=0,05, it means experiment class and control class have same ability. And for post-test, mean value of the experimental class was 81,60 and for the control class was 74,30. From the calculation of t-test one side, obtained tcount<ttable=2,895<1,671 using Î±=0,05 So, there was the effect of Discovery Learning model on students™ learning outcoes of Work and Energy material in class X SMA Negeri 1 Saipar Dolok Hole.